2022
DOI: 10.1186/s12904-022-01098-w
|View full text |Cite
|
Sign up to set email alerts
|

A study of the factors associated with emergency department visits in advanced cancer patients receiving palliative care

Abstract: Purpose Several studies demonstrated that cancer patients visited the emergency department (ED) frequently. This indicates unmet needs and poor-quality palliative care. We aimed to investigate the factors that contribute to ED visits among patients with advanced cancer in order to identify strategies for reducing unnecessary ED visits among these patients. Methods A retrospective study was conducted between January and December, 2019. Eligible pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…We found similarly high mortality rates among our patients, with the majority having died within 30 days of their last ED visit (59.9 % and 53.8, among our BPC and HC patients, respectively.) The frequency of cancer type distribution among our patient population, with colorectal, respiratory, and urogenital cancer being most common among them, was similar to other studies [ 33 ], and is in line with the most common causes of cancer mortality in the developed world.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found similarly high mortality rates among our patients, with the majority having died within 30 days of their last ED visit (59.9 % and 53.8, among our BPC and HC patients, respectively.) The frequency of cancer type distribution among our patient population, with colorectal, respiratory, and urogenital cancer being most common among them, was similar to other studies [ 33 ], and is in line with the most common causes of cancer mortality in the developed world.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the majority of patients receiving BPC or HC were over 65 years old, and slightly more female patients (55 %) visited the ED according. A recent ivestiagtion regarding the emergency department visits of patients with cancer receiving palliative care found that the mean age of patients was 65.5 years and there was a slight majority of men (50.7 %) [ 27 ] as was also found in other previous studies that men were more likely to visit the ED at the end of life [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 77%
“…Conversely, patients with a Palliative Performance Scale between 50% and 90% were more likely to visit the ED. 17 In our study, there were fewer missed opportunities for cancer patients than for patients with other diseases, possibly because ED staff perceive or recognize cancer as a chronic and mostly non-curable disease. Furthermore, there are many studies about PC for cancer 7,23,24 in the ED.…”
mentioning
confidence: 60%
“…Conversely, patients with a Palliative Performance Scale between 50% and 90% were more likely to visit the ED. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation